2018
DOI: 10.1103/physreva.98.023426
|View full text |Cite
|
Sign up to set email alerts
|

Multiple ionization of argon via multi-XUV-photon absorption induced by 20-GW high-order harmonic laser pulses

Abstract: We report the observation of multiple ionization of argon through multi-XUV-photon absorption induced by an unprecedentedly powerful laser driven high-order harmonic generation source. Comparing the measured intensity dependence of the yield of the different argon charge states with numerical calculations we can infer the different channels-direct and sequential-underlying the interaction. While such studies were feasible so far only with free electron laser (FEL) sources, this paper connects highly nonlinear … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 45 publications
2
63
2
Order By: Relevance
“…Our findings demonstrate that we achieve a higher degree of ionization, although our XUV pulse energy is more than two orders of magnitude lower than the pulse energy reported in Ref. [12]. Our results therefore open a path for the investigation of highly nonlinear processes in the XUV range using HHG sources that are driven by lasers with moderately high pulse energies, which makes it straightforward to perform these experiments using lasers at kHz repetition rates in the future.…”
mentioning
confidence: 51%
“…Our findings demonstrate that we achieve a higher degree of ionization, although our XUV pulse energy is more than two orders of magnitude lower than the pulse energy reported in Ref. [12]. Our results therefore open a path for the investigation of highly nonlinear processes in the XUV range using HHG sources that are driven by lasers with moderately high pulse energies, which makes it straightforward to perform these experiments using lasers at kHz repetition rates in the future.…”
mentioning
confidence: 51%
“…The high XUV-photon flux beam-line mentioned in the previous section has been recently developed and tested in the Attosecond Science & Technology laboratory of FORTH-IESL 59 . In this section, a detailed description of the beam line and its characterization is presented.…”
Section: The High Xuv Photon Flux Sourcementioning
confidence: 99%
“…At the same time it has been recently shown that multi-cycle high peak power laser beams, focused in the generation medium using long focal lengths of several meters, in combination with quasi-phase matching 58 arrangements, achieved through a chain of small length gas media i.e. pulsed gas jets, can reach emission of 20-GW XUV harmonic power at the source in the spectral region of 15-30 eV 59 . In the work of Nayak et al apart from the measurement of the harmonic source power the high focused XUV intensities achieved were evidenced through the observation of multi-XUV-photon multiple ionization of argon atoms.…”
mentioning
confidence: 99%
“…The present study allows the precise direct measurement of the XUV beam divergence generated in gas phase media. In addition, it can provide quantitative information during the coherent synthesis of sequentially positioned high harmonic sources when different phase matching and quasi-phase matching approaches are employed [18]. These approaches are directly connected to the improvement of the coherence properties and the photon flux of the attosecond pulses.…”
Section: Introductionmentioning
confidence: 99%